Literature of impasse : a comparative analysis of Joseph Roth’s Radetzkymarsch, Giorgio Bassani’s Gli Occhiali d’Oro and Henri Fauconnier’s Malaisie - Snyman, Jacobus Wilhelmus Otto (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.